Povo Sacerdotal - Pereira, Ney Brasil (Revista Encontros Teológicos, 2016)
Resumo: Após uma introdução, em que situa o tema, no contexto do “Ano Sacerdotal”, o autor examina a incidência do conceito de “povo sacerdotal” no Antigo e no Novo Testamento, o que constitui o núcleo do artigo, em duas partes. Na conclusão, apresenta o sacerdócio ministerial, dos presbíteros, a serviço do “povo sacerdotal”. Abstract: The article begins with the presentation of the Year dedicated to the priesthood, and widens its focus paying tribute to the idea of the “priestly people” both of the Old and New Testament. With this perspective in mind the nucleus of the article is set forth in two parts. In the conclusion several issues come to the fore, such as the ministerial priesthood and the presbyters at the service of the “priestly people.